The Implementation Of The LMD System In The Algerian Higher Education Context:Reform And Resistance (El-Wahat Journal for Research and Studies, 2017)
The New Reform Or The "LMD"System Is Only A Copy Of The French Model (Licence, Master, Doctorat). By Virtue Of An Executive Decree In 2004, Many Universities In Our Country Have Been Undertaking The Reforms, Working Together With Many European Universities. The Local Authorities Hope That The New System Will Facilitate The International Mobility Of Algerian Intellectuals; That It Will Offer Tremendous Opportunities For Students To Choose Freely The Fields They Desire To Specialise In; And That, In The Long Run, It Will Make The Learning Outcomes More Corresponding To The Needs Of The Labour Market.The Efforts Of The Ministry Of Higher Education Do Not Only Lie In The Re-Foundation Of The Programmes And Evaluation Or Assessment Standards, But Also In Creating Adequate Learning And Teaching Methods. Many Experts, In This Same Vein, Deem That Algeria Is A Part Of This World And As Such Political, Economic And Pedagogical Measures Must Be Taken; They Foresee That Openness To The World And Competitiveness Are Best Achieved Via Repositioned Education. However, On The Ground, These Aspirations Have Met Resistance And, At Times, Refusal On The Part Of Practitioners. This State Has Led To Confusion About The Prospects And Future Of The LMD System In Algeria. It Is Within The Scope Of The Present Study That The Researchers Intendto Highlight The University Community’s Attitudes Towards, And Perceptions Of The New Project. Key Terms  - LMD System, Higher Education, Algerian Universities, Reform, Resistance,Attitudes, Perceptions.